The functional role of Notch signaling in HPV-mediated transformation is dose-dependent and linked to AP-1 alterations - Henken, Florianne E. (Springer Netherlands, 2012)
BACKGROUND: The role of Notch signaling in HPV-mediated transformation has been a long standing debate, as both tumor suppressive and oncogenic properties have been described. We examined whether the dual findings in literature may be explained by gene dosage effects and determined the relation with AP-1, a downstream target of Notch. METHODS: SiHa cervical cancer cells were transfected with two doses of intracellular active Notch. Non-tumorigenic HPV16-immortalized keratinocytes (FK16A) were transfected with Fra1 specific siRNAs and non-targeting controls. Transfectants were analysed for Notch, Hes, cJun, cFos and Fra1 mRNA expression, Notch pathway activation using luciferase assays, cell viability using MTT assays, anchorage independent growth, AP-1 activity and/or AP-1 complex composition using EMSA. RESULTS: In SiHa cells two activation states of Notch signaling pathway were obtained. Moderate Notch activation contributed to increased viability and anchorage independent growth, whereas high level Notch activation decreased anchorage independent growth. The shift in phenotypical outcome was correlated to altered AP-1 activity and complex composition. Moderate Notch expression led to an increased AP-1 transcriptional activity and DNA binding activity, but did not affect complex composition. High levels of Notch additionally led to a change in AP-1 complex composition, from cJun/cFos to cJun/Fra1 dimers, which is exemplary for non-tumorigenic HPV-immortalized cell lines. Conversely, silencing of Fra1 in non-tumorigenic HPV16-immortalized keratinocytes, leading to an enrichment of cJun/cFos dimers, was accompanied with increased colony formation. CONCLUSION: The functional role of Notch in HPV-mediated transformation is dosage dependent and correlated to a change in AP-1.